Cell adhesion and polarisation on molecularly defined spacing gradient surfaces of cyclic RGDfK peptide patches - Jakubick, Vera C. (2008)
A combination of soluble and extracellular matrix (ECM)-immobilised molecular gradients steer cell migration and location in vivo. Here, gradients of ECM molecules are formed in vitro by the combination of a surface nanopatterning technique called block copolymer nanolithography (BCN) and a biofunctionalisation technique. A modified substrate dip coating process of BCN allows for the formation of precise molecular gradients of cyclic RGDfK peptide patches at interfaces which are presented to cells for testing cell adhesion and polarisation. Surfaces formed by BCN consist of hexagonally ordered gold dot patterns with a gradient in particle spacing. Each dot serves as a chemical anchor for the binding of cyclic RGDfK peptides which are specifically recognised by α(v)β(3) integrins. Due to steric hindrance only up to one integrin binds to one functionalised gold dot. Applying particle spacing gradients we demonstrate how cell morphology, adhesion area, actin and vinculin distribution as well as polarisation are influenced by the peptide patch spacing gradient. As a consequence, these gradients of adhesive ligands induce cell orientation towards smaller particle spacing when the gradient strength is 15 nm/mm at least. Eventually, this measures a minimal value of ligand patch spacing sensitivity of adhesive cells which is approximately 1 nm across the cell body.